К вопросу изучения фауны мягкотелок (Coleoptera, Cantharidae) Крыма - Истомина, Л.П. (Вестник зоологии, 1969)
The results are presented of studying the fauna of the family Cantharidae in the Crimea. 29 species of Cantharidae were found in the explored territory. Catitharis li-vida L., Rhagonycha femoralis В r u l., Rh. fulva Scop, are the most common and widely distributed. C. pallida G z., Rh. limbata Thoms., Rh. nigripes R e d t. and Malthinus fasciatus О 1. are mentioned for the first time for the Crimea. Most species are mesophyls predominating on the glades, borders of forests, meadows with thick grass stand; some species are confined to the plots with woody-shrub vegetation.